Influence of rest duration on muscle activation during submaximal intermittent contractions with the elbow flexor muscles - Mendez-Villanueva, A.; Baudry, S.; Riley, Z. A.; Rudroff, T. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM:The purpose of the study was to compare the influence of two intervals between consecutive intermittent contractions with the elbow flexors on time to failure and the accompanying changes in electromyographic (EMG) activity and excitation-contraction coupling. METHODS:Subjects performed 6-s intermittent isometric contractions at 50% of the maximal voluntary contraction (MVC) force to task failure in two sessions. The recovery period between consecutive contractions was 4-s (short recovery protocol, SRP) in one and 14-s (long recovery protocol, LRP) in the other session. RESULTS: The number of contractions performed to task failure was greater for the LRP (99±24) compared with the SRP (46±18; P<0.05). The amplitude and duration of the maximal compound action potential (M-wave) did not change during either protocol. EMG activity (% peak MVC) for the elbow flexors and the force fluctuations increased more rapidly during the SRP compared with the LRP (P<0.05) and was greater at task failure for the SRP protocol (P<0.05). These changes were accompanied by a faster decline in twitch force. CONCLUSIONS:The results indicate that a briefer interval between consecutive contractions was associated with a more rapid impairment of the excitation-contraction coupling and a faster increase in muscle activation, despite a similar net muscle force for the two protocols.